FAILURE ANALYSIS AND OPTIMIZATION OF A HIGH FREQUENCY VIBRATION TOOL - WANG Yong; CHEN Sheng; WANG Qi; ZHENG WeiHua; QIU JunGuang (Jixie qiangdu)
The High-frequency vibration tool is widely used in the packaging, footwear and other industries to make samples. At high speed, the tool often fails to meet the requirements due to noise and inaccuracy. Based on flexible multi-body systems dynamics theory and combined finite element analysis simulation method, a rigid-flexible coupling model of the high frequency vibrating tool was developed. Several useful conclusions are drawn that the reasons for tool failure are uneven stress on the eccentric shaft sleeve and big deformation for the linkage coincided with the practical. It also verified the model accuracy. Meanwhile, the flexible rod free mode and the tool mode under the constraint were analyzed, the resonance vibration frequency was obtained. The structure was improved by dynamic balance method, which effectively increased the operating frequency by balancing a part of mechanism inertial force and laid a theoretical foundation for the tool advanced optimization.